Characterization of the protein gp1 from bacteriophage φIN93 - Matsushita, Isao; Yanase, Hideshi (Biological Letters, 2011)
The protein gp1, encoded by the ORF1 gene in the genome of the Thermus phage φIN93, is similar to the replication protein encoded by repA in the Thermus sp. plasmid. To confirm that gp1 functions as a replication protein, we constructed the recombinant plasmid pIA1, by inserting ORF1 and the kanamycin acetyltransferase (kat) gene into pBluescriptII SK(+), which enabled replication of pIA1 in Thermus thermophilus HB27. By contrast, plasmid pIA1-del, which contained only a part of ORF1 (the other part deleted using KpnI), was not replicated. These results show that gp1 functions as a replication protein and that pIA1 can be used as a shuttle vector between Thermus thermophilus HB27 and Escherichia coli.